"Aiding Defeated Migrants": Institutional Strategies to Assist Polish Returned Migrants. (5th December 2013) - Czerniejewska, Izabela; Goździak, Elżbieta M.
Abstract This article is based on an exploratory study of Polish "returned" migrants aided by the Barka Foundation, carried out in 2010 shortly after the men were returned to Poland, during the liminal stage of readjustment and decision‐making about whether to remain in Poland, return to the UK or migrate elsewhere. The interviews centred on migrants' assessment of their migration projects; engagement with Barka outreach workers; decision‐making processes about returning to Poland; assessment of most pressing needs; evaluation of provided services once they returned to Poland; and plans for the future. Discussions with service providers mirrored these themes to compare the emic or insiders' (migrants) and etic or outsiders' (programme staff's) assessment of the strategies employed to aid Polish "returned" migrants.